Use and understanding of labelling information when preparing infant formula: Evidence from interviews and eye tracking. (May 2020) - Malek, Lenka; Duffy, Gillian; Fowler, Hazel; Katzer, Lisa
Graphical abstract: Highlights: Preparation instructions on infant formula are often understood but not followed. The main reason given for non-adherence is convenience. Non-adherence is also due to lack of awareness and low perceived risks to infants. Mandated food-safety elements need to be more noticeable, clear and specific. Abstract: There are various risks associated with incorrect preparation and storage of infant formula, including microbiological hazards. Preparing and storing reconstituted infant formula correctly can reduce potential risks. The product label on infant formula is often the main source of information for caregivers on the correct handling of infant formula. Caregivers' ability to understand and follow preparation and storage instructions is, therefore, of high importance in the safe use of infant formula. This study aims to increase understanding of how Australian caregivers perceive, interpret and use mandatory and voluntary "on-pack" label information when preparing and storing infant formula. An eye-tracking task requiring caregivers (n = 30) to prepare an unfamiliar infant formula product while wearing Tobi Pro 2 Glasses revealed that almost all caregivers look at the preparation instructions (93%), though fewer look at the warning advice (43%) and storage instructions (27%). Findings from retrospective think-aloud and in-depth interviews conducted immediately after the eye-tracking task, revealed that while preparation instructions are generally understood, they are not always adhered to, with most caregivers making modifications for convenience. Lack of awareness and low perceived risk to the infant's health were other reasons for non-adherence. These findings suggest that mandated food-safety elements on infant formula products need to be more noticeable, clearer and more specific with respect to potential infant health risks associated with non-adherence, to ensure safe preparation and storage by all caregivers. These findings will be used to inform a review of the labelling requirements for infant formula products.